Two-dimensional geometry of spin excitations in the high-transition-temperature superconductor YBa2Cu3O6+x - Hinkov, V.; Pailhès, S.; Bourges, P.; Sidis, Y.; Ivanov, A.; Kulakov, A.; Lin, C. T.; Chen, D. P.; Bernhard, C.; Keimer, B. (Nature (London), 2004)
The fundamental building block of the copper oxide superconductors is a Cu 4 O 4 square plaquette. The plaquettes in most of these materials are slightly distorted to form a rectangular lattice, for which an influential theory predicts that high-transition-temperature (high- T c ) superconductivity is nucleated in ‘stripes’ aligned along one of the axes 1 , 2 , 3 . This theory received strong support from experiments that indicated a one-dimensional character for the magnetic excitations in the high- T c material YBa 2 Cu 3 O 6.6 (ref. 4 ). Here we report neutron scattering data on ‘untwinned’ YBa 2 Cu 3 O 6+ x crystals, in which the orientation of the rectangular lattice is maintained throughout the entire volume. Contrary to the earlier claim 4 , we demonstrate that the geometry of the magnetic fluctuations is two-dimensional. Rigid stripe arrays therefore appear to be ruled out over a wide range of doping levels in YBa 2 Cu 3 O 6+ x , but the data may be consistent with liquid-crystalline stripe order 5 . The debate about stripes has therefore been reopened.